Right for the wrong reason; wrong for the right reason: Gibson and Arnheim on picture perception - Verstegen, Ian (Public Journal of Semiotics, 2021)
Although J J Gibson’s theory of picture perception was often crude and biased toward naturalism, its fundamental division between the visual world and the visual field made it a semiotic theory. Contrariwise, although Arnheim wrote sensitively on pictures, he never seemed to admit that they were signs. This paper reviews both Gibson’s and Arnheim’s theories of picture perception, and explains where Arnheim’s biases caused him to lose the possibility of framing his approach in the most basic semiotic terms. Nevertheless, using the phenomenological semiotics of Sonesson and his theory of the Lifeworld Hierarchy, I demonstrate latent semiotic elements in Arnheim’s theory, due perhaps to Alfred Schutz’s influence. Hoping to argue against the brute theory of denotation, Arnheim instead sought to delay invocation of (conventional) signs as long as possible, and his idea of iconic pictorialization assumes but does not name signification. Nevertheless, I propose that Arnheim has a kind of theory of the Lifeworld Hierarchy inside the picture. Thus, he (wrongly) does not see the picture as overtly signifying but interestingly gives hints about how to treat the objects of the virtual world of the picture based on their relationship to the overall style of the work.